Leadership styles, organizational commitment and job satisfaction among co-curricular teachers in secondary schools in Malaysia - Abdul Halim, Norhaily (2019)
This study was conducted to explore the different leadership styles of Senior Assistants of Co-curricular and the level of co-curricular teachers’organizational commitment and job satisfaction. Besides, the study aimed to identify the relationship between Senior Assistants of Co-curricular leadership styles and co-curricular teachers’ job satisfaction and organizational commitment. In addition, it examined the role of job satisfaction as mediators of the relationship. The study utilized proportional stratified random sampling method and the respondents are 381 co-curricular teachers. The instruments are the Multifactor Leadership Questionnaire (MLQ 5X Short Form) by Bass and Avolio (1995), the Organizational Commitment Questionnaire (OCQ) by Meyer and Allen (1997) and the Job Satisfaction Survey (JSS) by Spector (1994).Data obtained were analyzed using descriptive statistics, Product moment correlation coefficient, Pearson r and the Structural Equation Modeling (SEM). The results of the study showed that Senior Assistants of Co-curricular exhibited transformational and transactional leadership styles at a high levelwhile passive avoidant leadership was exhibited at a low level. The findings of the study showed that the level of job satisfaction and organizational commitment of co-curricular teachers are moderate.The result of correlation analysis indicated that there was a positive but weak relationship between transformational leadership and organizational commitment. The findings showed that there was a positive but weak relationship between transactional leadership and organizational commitment. Meanwhile, passive avoidant leadership wasfound to have no relationship with organizational commitment. The study also revealed that there was a positiveand strong relationship between both transformational and transactional leadership with job satisfaction. However, the relationship between passive avoidant leadership and job satisfaction was reported as a negativeand weak relationship. The study also exhibited that there was a positiverelationship between job satisfaction and organizational commitment. The result of SEM analysis indicated that job satisfaction is a mediator in the relationship between transformational, transactional and passive avoidant leadership with organizational commitment and the mediation is a full mediation. Findings can be used to improve school administrators’ general strategies. Senior Assistants of Co-curricular in particular and other school administrators in general shouldbetrained to be transformational and transactional leaders. Senior Assistants of Co-curricular in regular secondary schools in Malaysia should strive to bend the recognition of transactional leadership behaviour and hike up the recognition of transformational leadership to enhance job satisfaction and organizational commitment among co-curricular teachers. Besides, the Ministry of Education should pay greater attention to co-curricularteachers’ job satisfaction since job satisfaction fully mediates the relationship between leadership and organizational commitment.Thus, the leadership styles of Senior Assistance of Co-curricular is important to ensure co-curricular teachers commitment to the schools.